C5 Motor Palsy After Single- and Multi-level Anterior Cervical Diskectomy and Fusion: A Retrospective Review. Issue 8 (15th April 2019) - Wagner, Scott C.; Sebastian, Arjun S.; Butler, Joseph S.; Kaye, Ian D.; Morrissey, Patrick B.; Hilibrand, Alan S.; Vaccaro, Alexander R.; Kepler, Christopher K.
Abstract : Introduction: Postoperative C5 nerve root palsy is a known complication after cervical surgery. The effect of increasing number of levels fused on the prevalence of C5 palsy after anterior cervical diskectomy and fusion (ACDF) is unclear. Methods: Medical records of ACDF patients that included the C4-5 level at one institution were retrospectively reviewed. C5 palsy was defined as motor decline of the deltoid and/or biceps brachii muscle function by at least 1 level on standard manual muscle testing. Results: A total of 196 patients met the inclusion criteria, with no significant differences noted between groups undergoing single- or multi-level ACDF. The overall C5 palsy rate was 5.1%. Palsy rates were not statistically significant based on the number of levels fused. Six of the 10 patients with C5 palsy had complete recovery of motor strength, whereas 2 patients had at least some level of strength recovery. Conclusion: The overall C5 palsy rate was 5.1% for all patients undergoing up to four-level ACDF. The rate of postoperative motor decline was lowest in the patients undergoing two-level ACDF and highest in the single-level group, but this finding did not reach statistical significance. The prognosis for strength recovery by final follow-up is excellent. Level of Evidence: Level III, Case-control